PENELUSURAN ZAT TOKSIK SARANG SEMUT ACEH (Mymercodia sp) DENGAN METODE BST TERHADAP LARVA UDANG Artemia salina - Frengki Frengki; Cut Gina Indriyani (Faculty of Pharmacy, Universitas Muslim Indonesia, 2014)
The Myrmecodia species as medicinal plants find Papua Island and Sumatera Island like Aceh forest.It is a member of Rubiaceae family and lives as ephyphyte on other plants. Local peoples in Aceh province boiled the tubers parts of myrmecodia species to treat inflammation, rheumatic,cancer and other diseases. Meanwhile, there is still limited scientific evidence to proof the efficacy of myrmecodia species. The dried simplicia was extracted using maceration technique, then partitioned usingn-hexane, chloroform and n-buthanol solvent. Toxicity test was done by the Brine Shrimp Lethality Test (BST) methodat four concentration levels, i.e: 1000, 500, 250, 125 and 6.5 ppm. The result of the research showed that n-buthanol, chloroform and n-hexan of Myrmecodia sphad acute toxicity by LC50 value 97.72 ppm, 262.02 ppm and 223.87 ppm respectively. Analysis Infrared spectrum of buthanol extract showed some functional groups. like hydroxy, aether and aromatic ring.